Patient Choice of Nonsurgical Treatment Contributes to Disparities in Head and Neck Squamous Cell Carcinoma. (June 2018) - Parhar, Harman S.; Anderson, Donald W.; Janjua, Arif S.; Durham, J. Scott; Prisman, Eitan
Objectives: There are well-established outcome disparities among different demographic groups with head and neck squamous cell carcinoma (HNSCC). We aimed to investigate the potential contribution of patient choice of nonsurgical treatment to these disparities by estimating the rate of this phenomenon, identifying its predictors, and estimating the effect on cancer-specific survival. Study Design: Retrospective nationwide analysis. Settings: Surveillance, Epidemiology, and End Results Database (2004-2014). Subjects and Methods: Patients with HNSCC, who were recommended for primary surgery, were included. Multivariable logistic regression was used to identify demographic and clinical factors associated with patient choice of nonsurgical treatment, and Kaplan Meier/Cox regression was used to analyze survival. Results: Of 114, 506 patients with HNSCC, 58, 816 (51.4%) were recommended for primary surgery, and of those, 1550 (2.7%) chose nonsurgical treatment. Those who chose nonsurgical treatment were more likely to be older (67.1 ± 12.6 vs 63.6 ± 13.1, P < .01), were of Black (odds ratio [OR], 1.49; 95% confidence interval [CI], 1.28-1.74) or Asian (OR = 1.79; 95% CI, 1.46-2.20) ethnicity, were unmarried (OR married, 0.50; 95% CI, 0.44-0.58), had an advanced tumor, and had a hypopharyngeal or laryngeal primary. Choice of nonsurgical treatment imparted a 2.16-fold (95% CI, 2.02-2.30) increased risk of cancer-specific death. Conclusion: Of the patients, 2.7% chose nonsurgical treatment despite a provider recommendation that impairs survival. Choice of nonsurgical treatment is associated with older age, having Black or Asian ethnicity, being unmarried, having an advanced stage tumor, and having a primary site in the hypopharynx or larynx. Knowledge of these disparities may help providers counsel patients and help patients make informed decisions.